Математичне моделювання "зняття-відновлення" напруги на струмоприймачі електровозів постійного струму - Михаліченко, П.Є. (Технічна електродинаміка, 2012)
The mathematical model of electromagnetic processes in the system of electric traction of direct current in the mode of «break-off - touch» current collector electro-mobile unit is created. By integration of the system of differential equalizations of the electromagnetic state, dependences of transitional electric sizes in the power circuits of hauling substations and electric locomotive are got.